An Evaluation Of The Cambridge English For Job Hunting Textbook Through The Lens Of Tomlinson's Theory: A Comprehensive Analysis Of Content And Effectiveness - Abdul Syahid; Josilia Puspito Rahayu; Muhamad Ario Setiawan; Rizki Novia Darma; Syarif Hidayat (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study is aimed to investigate the compatibility of materials in the textbook entitled